Analisis Pemahaman Guru Terhadap Anak Berkebutuhan Khusus - Karlina Wong Lieung; Dewi Puji Rahayu; Agus Kichi Hermansyah (Musamus Journal of Primary Education, 2021)
Every child has the right to receive basic education without exception. Elementary schools provide services for all children, both normal in general and children with special needs. This argument is reinforced by the Convention on the Rights of Persons with Disabilities which calls for inclusive education to be very important. In fact, many elementary schools have not been able to provide services for children with special needs. Teachers feel unable to provide educational services for children with special needs who attend regular schools. This study aims to explore information about teachers' understanding of children with special needs and their types. This research used descriptive qualitative research. The data were collected through interviews through the Google Form media and WhatsApp application with source triangulation. The participants were 28 teachers of four schools in Merauke city. The results showed that 92.9% of teachers already knew information about children with special needs in general. However, most of the participants cannot distinguish the characteristics of each type of crew well. It causes teachers to have difficulty in providing appropriate educational services.